A Case Study of Lance-Adams Syndrome. (3rd July 2021) - Shugan, Adam
ABSTRACT: Lance-Adams syndrome (LAS) was first described in 1963 by Lance and Adams, who cited four cases of posthypoxic action myoclonus. Since then, less than 150 cases have been reported world-wide. LAS differs from acute posthypoxic myoclonus, which usually occurs within twelve hours of the anoxic event, with the patient remaining in a deep coma with an extremely poor prognosis. Patients with LAS retain neurological function and develop myoclonus days or weeks after their hypoxic event. This report describes the case of a 64-year-old male who developed LAS following cardiac arrest. His progression from ICU to outpatient was followed through multiple electroencephalograms.